"Najboljše, da me imate kar pod očeta" - Humer, Živa (Socialno delo, 2021)
In the context of involved fatherhood, we focus in this article on parental stories and experiences of gay fathers in caring for children. Based on an analysis of four interviews with gay fathers, their experiences of fatherhood and fathering, child care, and parenting rights are presented, which show the inequalities and discrimination they're faced with. Gay fathers' narratives of care practices point to parenting and childcare practices as a key identity point in their lives. Through primary parenting, involvement in the child's life and childcare practices, gay fathers are expanding involved fatherhood and co-create a model of caring masculinities based on intimacy, care practices, relationships and reciprocity.
Keywords: caring masculinities; discrimination; diskriminacija; družine; families; fatherhood; gays; geji; očetovstvo; skrbne moškosti